A Black British Canon?
XIII, 213 p.
Keywords: This much-needed collection examines the formation of a black British canon including writers, dramatists, film-makers and artists. Contributors including John McLeod, Michael McMillan, Mike Phillips and Alison Donnell discuss the textual, political and cultural history of black British and the term 'black British' itself.